Plasma concentration of proneurotensin and prediction of cause-specific mortality in a middle aged cohort during long-term follow-up. (14th October 2021) - Fawad, A; Butt, Z; Bergmann, A; Schulte, J; Nilsson, P; Bennet, L; Melander, M; Melander, O
Abstract: Purpose: To examine the prediction of proneurotensin (Pro-NT) on total and cause-specific mortality in a middle-aged cohort. Methods: In the population-based middle-aged cohort (n=4632 participants, mean age 57 years) of the Malmo Diet and Cancer (MDC) study, Pro-NT was assessed and total- as well as cause-specific mortality were studied. Main cause of death were based on the International Classification of Diseases (ICD). Assessments were done using Cox proportional hazards models adjusted for age and sex. Results: During a mean follow-up of 20±3 years, 950 men and 956 women died. There was a significantly increased risk of total mortality in subjects belonging to quartile 4 of Pro-NT (Pro-NT ≥149 pmol/L) compared with quartiles 1–3 (Pro-NT <149 pmol/L), hazard ratio (HR) of 1.29 (95% confidence interval [CI] 1.17–1.42; P<0.001) after adjustment for age and sex. No significant interaction was observed between Pro-NT and gender on total mortality. Individuals within quartile 4 vs. quartiles 1–3 had a HR of 1.41 (95% CI 1.18–1.68; P<0.001) for death due to cardiovascular diseases (n=595/4632), 2.53 (95% CI 1.37–4.67; P=0.003) due to digestive tract diseases (n=42/4632), 1.62 (95% CI 1.04–2.52; P=0.032) due to mental and behavioural diseases (n=90/4632), and 1.91 (95% CI 1.15–3.19; P=0.013) due to unspecific causes of death (n=64/4632). No significant relationships between Pro-NT and deaths due to cancer, infections, neurological or other causes were observed. Adjustments for cardiovascular risk factors only marginally changed these results. Conclusions: Pro-NT is a predictor of total mortality and the increased risk is driven by deaths due to cardiovascular- digestive tract- mental and behavioural diseases, as well as deaths attributed to unspecific causes. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Knut and Alice Wallenberg Foundationthe Swedish Heart and Lung Foundation.